A SURVEY OF ENDO-PARASITE AND BLOOD PARASITE OF SYNODONTIS SCHALL (BLOCH & SCHNEIDER, 1801) FROM OTUOGORI RIVER IN OGBIA, BAYELSA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Fishes are a source of protein to human and also provide a means of occupation for the people. Fish parasites are of public health importance, reducing fish population and thereby, resulting in loss of protein source and jobs. This study aimed to reveal the presence of various endo-parasites and blood parasites in fish samples collected from Otuogori River using standard techniques. A total of 40 live fish, purchased weekly from a fisherwoman during early morning hours, from December 2022 to January 2023, contingent on availability, were transported immediately to the laboratory for parasitological examination with the sex noted and the standard length measured. Aliquot from teased internal organs and blood sample collected from caudal circulation of each fish were respectively smeared on clean slides and viewed under the microscope. The parasites detected were identified using an identification key. The study revealed that out of 40 Synodontis schall examined, 4 were infected with an overall prevalence of 10%. Females 3(14.29%) were more infected than males 1(5.26%) (p>0.05). Parasites recorded include Trypanosoma spp, Camallanus spp and Anisakid spp; with Trypanosoma spp. (50%) being the most prevalent.  The study result also showed that those with body length range of 9.2cm-14.2cm were infected the most (25%) (p>0.05). Fish samples weighing 55g-105g and those with body length range of 9.2cm-14.2cm had the highest mean intensity. Weight did not significantly affect the prevalence of infestation of the fishes (p>0.05). Fish samples collected from Otuogori River should be properly cooked before eaten to avoid zoonotic infections.
Keywords: Bayelsa; Fish parasites; River; Survey; Synodontis